Contact angle properties of bioacrylic palm oil based polyol for polyurethane coating - Ernie S.A.; Nurul N.M.N.; Farah W.H.; Syazana A.Z.; Norazwani M.Z. (Trans Tech Publications Ltd, 2024)
Indexed by Scopus/ERA